2014
DOI: 10.1208/s12249-014-0201-0
|View full text |Cite
|
Sign up to set email alerts
|

Serratiopeptidase Loaded Chitosan Nanoparticles by Polyelectrolyte Complexation: In Vitro and In Vivo Evaluation

Abstract: Abstract. The aim of the present study was to formulate serratiopeptidase (SER)-loaded chitosan (CS) nanoparticles for oral delivery. SER is a proteolytic enzyme which is very sensitive to change in temperature and pH. SER-loaded CS nanoparticles were fabricated by ionic gelation method using tripolyphosphate (TPP). Nanoparticles were characterized for its particle size, morphology, entrapment efficiency, loading efficiency, percent recovery, and in vitro dissolution study. SER-CS nanoparticles had a particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…2). This is in accordance with previous papers that confirmed that trehalose which is a non-reducing sugar could be the most preferable lyoprotectant of choice because of its merits over the other sugars; including a very low chemical reactivity, a higher glass transition temperature Tg, less hygroscopicity, in addition to the absence of internal hydrogen bounds, allowing a more flexible formation of hydrogen bonds with nanoparticles during the freeze-drying process (39). However, mannitol was proved to be more effective in obtaining a higher EE value according to our experimental work.…”
Section: Resultssupporting
confidence: 93%
“…2). This is in accordance with previous papers that confirmed that trehalose which is a non-reducing sugar could be the most preferable lyoprotectant of choice because of its merits over the other sugars; including a very low chemical reactivity, a higher glass transition temperature Tg, less hygroscopicity, in addition to the absence of internal hydrogen bounds, allowing a more flexible formation of hydrogen bonds with nanoparticles during the freeze-drying process (39). However, mannitol was proved to be more effective in obtaining a higher EE value according to our experimental work.…”
Section: Resultssupporting
confidence: 93%
“…In this study, EVOP, a powerful statistical design, was used to optimize the media composition for production of serratiopeptidase through fermentation by them. Serratiopeptidase encapsulation was carried out by Mali et al [24] with different concentrations of chitosan (CS) and tripolyphosphate (TPP) in which TPP acted as a cross-linking and condensing agent to obtain nanoparticles. Particle size could be modulated by changing concentrations of CS and TPP.…”
Section: Qualitative and Quantitative Analytical Techniques For Serramentioning
confidence: 99%
“…Además, se pudo demostrar que las Caro-León et al: Métodos de preparación de nanopartículas de quitosano / XXI (3): 13-25 (2019) nanopartículas aumentaron la concentración plasmática del fármaco y redujeron la formación de trombos en un modelo de trombosis venosa en ratas. Mali et al (2015) obtuvieron una formulación de nanopartículas de quitosano cargadas con serratiopeptidasa para administración oral. El tamaño promedio de los sistemas se encontraba en un rango de 400-600 nm con una eficiencia de asociación del 80% y capacidad de liberación controlada por 24 horas.…”
Section: Gelificación Ionotrópicaunclassified